Learner Autonomy and Internal Locus of Control: Influential Factors in EFL Context - Behnam Aghayani (Hasanuddin University, 2021)
Considering the significant role of learner autonomy and internal locus of control in language learning process, the present study attempted to investigate the correlation between EFL learners’ autonomy and internal locus of control. To achieve such aim, a sample of 95 Iranian EFL learners both male (n=33) and female (n=62) participated in this study. The instruments used in the present study were learner autonomy questionnaire (Learner Autonomy Perception Questionnaire) and internal locus of control questionnaire (Internal Locus of Control Index). The findings indicated a significant positive correlation among EFL learners’ autonomy and their internal locus of control. Moreover, this study highlights the importance of learner autonomy and internal locus of control in the foreign language learning and also aims to raise EFL teachers’ awareness of the importance of these two key factors in the EFL context. The suggestions related to the findings of the current study are discussed at the end of study.